2002
DOI: 10.1007/s00240-002-0254-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effects of exogenous nitric oxide versus antioxidant vitamins on renal ischemia reperfusion injury

Abstract: The objectives of this study were to compare the protective influence of exogenous nitric oxide on renal ischemia reperfusion (I/R) injury with that of the antioxidant vitamins C and E. Sprague-Dawley rats were divided into three groups ( n=12 per group). Normal saline solution was given in group 1, a vitamin C (200 mg/kg/d) plus vitamin E (100 mg/kg/d) combination in group 2 for 3 days before operating and Na-nitroprusside (5 mg/kg/d) in group 3 before reperfusion. The left kidneys were exposed to warm ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
3
14
0
Order By: Relevance
“…27 Previous studies have shown that I/R causes an increase in MDA levels and a decrease in GSH levels and SOD activity. 28,29 Similarly, we observed a significant decrease in GSH levels and SOD activity and an increase in MDA content during I/R-induced renal injury, making our findings agree with results from previous studies. In our study, infliximab tended to increase SOD activity and GSH levels.…”
Section: Discussionsupporting
confidence: 92%
“…27 Previous studies have shown that I/R causes an increase in MDA levels and a decrease in GSH levels and SOD activity. 28,29 Similarly, we observed a significant decrease in GSH levels and SOD activity and an increase in MDA content during I/R-induced renal injury, making our findings agree with results from previous studies. In our study, infliximab tended to increase SOD activity and GSH levels.…”
Section: Discussionsupporting
confidence: 92%
“…Following decreases in the level of GSH, oxidative stress increases and thereafter cell damage occurs. [36] Similarly, we showed a significant reduction in GSH level in the kidney of rats during I/R. Furthermore, pretreatment with AA prevented the severe depletion of GSH in the renal I/R treated rats.…”
Section: Discussionsupporting
confidence: 70%
“…Our finding was similar to that of previous studies. [5,23] Unal et al [5] observed that vitamin C+E had some antioxidative effects on the reperfusion injury, though a statistically significant, positive effect could not be demonstrated in the histopathological evaluations. Also Irmak et al [23] studied the effect of caffeic phenethyl ester (CAPE) on ischemiareperfusion in comparison with vitamin E. Morphological damage was clearly observed in the kidneys of the IR group.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] These free radicals can attack a wide variety of cellular components, including DNA, proteins, and membrane lipids. [3] Cellular defense against free radical injury is provided by enzymatic (catalase, superoxide dismutases, and glutathione peroxidase) and nonenzymatic (GSH, vitamin E, vitamin C, and urate) free radical scavenging systems, present in the cell.…”
Section: T Aktoz Et Almentioning
confidence: 99%